SKEMATIK DESAIN ARSITEKTUR FASILITAS PENUNJANG AGROWISATA BUDIDAYA LEBAH MADU (STUDI KASUS: DESA MADENAN, KABUPATEN BULELENG) - Made Wahyu Anggareza Sumarna; Ni Wayan Meidayanti Mustika; I Wayan Wirya Sastrawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2020)
Agro-tourism exists as a tourist attraction with the use of natural resources including farms and animal husbandry, empowerment of rural communities with work as farmers have a place to increase production from agricultural and livestock products that can boost their social economy. Madenan Village, Buleleng Regency is a potential area in the agropolitan sector. Of the many agro-tourism in Bali, Honey Bees Cultivation in Madenan Village is very likely, in addition to being quite unique, the impact on the socioeconomic and the environment will be felt, especially the government supports this in the form of superior Honey Bee Bees, but its management has not been precise so that it impacts to the decline in production. Efforts to facilitate farmers in the cultivation of Honey Bees, Agro Tourism is an answer to solve architectural problems regarding production and management. The concept of edu - tourism will be an attraction in this agro-tourism with the form of buildings that adapt to the climate that will be applied. Tropical Architecture with adjustment of humid climate conditions with mountain topography will be an architectural solution in the Madenan Village area. Keywords: agro-tourism, beekeeping, edu-tourism, tropical